Testing for indeterminacy: An application to US monetary policy - Thomas A. Lubik; Frank Schorfheide (The Johns Hopkins University, Department of Economics, 2002)
This paper considers a prototypical monetary business cycle model for the U.S. economy, in which the equilibrium is undetermined if monetary policy is `inactive? In previous multivariate studies it has been common practice to restrict parameter estimates to values for which the equilibrium is unique. We show how the likelihood-based estimation of dynamic stochastic general equilibrium models can be extended to allow for indeterminacies and sunspot fluctuations. We propose a posterior odds test for the hypothesis that the data are best explained by parameters that imply determinacy. Our empirical results show that the Volcker-Greenspan policy regime is consistent with determinacy, whereas the pre-Volcker regime is not. We find that before 1979 non-fundamental sunspot shocks may have contributed significantly to inflation and interest rate volatility, but essentially did not affect output fluctuations.
Keywords: C11; C52; C62; E52; 330; Econometric Evaluation and Testing; Rational Expectations Models; Indeterminacy; Monetary DSGE Models; Konjunkturtheorie; Geldpolitik; Dynamisches Gleichgewicht; Schätzung; USA; Gleichgewicht